2007
DOI: 10.5433/1679-0359.2007v28n1p29
|View full text |Cite
|
Sign up to set email alerts
|

Atividades antibacteriana, antifúngica e indutora de fitoalexinas de hidrolatos de plantas medicinais

Abstract: ResumoO objetivo do trabalho foi avaliar a atividade como antifúngico, antibacteriano e indutor da produção de fitoalexinas dos hidrolatos de Helietta apiculata (canela-de-veado) (HA), Conyza canadensis (buva) (CC) e Cymbopogon nardus (citronela) (CN) nas concentrações de 1, 5, 10, 15, 20 e 25%, buscando seu uso no controle alternativo de doenças em plantas. Para o ensaio de fitoalexinas foram utilizados mesocótilos estiolados de sorgo. Para o efeito antibacteriano foi avaliado o crescimento da bactéria Xantho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 5 publications
0
5
0
5
Order By: Relevance
“…1,6 Given the importance of developing new biopesticides and investigating their spectra of action, a recent survey showed promising results with the allelopathic plant Conyza canadensis (L.) Cronquist, which belongs to the Asteraceae family and is popularly known as horseweed. 7 This plant is a potential source of bioactive compounds 8 and several studies have reported the fungitoxic effects of its essential oils, [9][10][11] although the compounds responsible for such activity were not identified. Queiroz et al 7 found three fungitoxic compounds in dichloromethane extracts of C. canadensis specimens collected in the USA: (4Z)-lachnophyllum lactone (1), (4Z,8Z)-matricaria lactone (2), and (2Z,8Z)-matricaria acid methyl ester (3), whose chemical structures are shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…1,6 Given the importance of developing new biopesticides and investigating their spectra of action, a recent survey showed promising results with the allelopathic plant Conyza canadensis (L.) Cronquist, which belongs to the Asteraceae family and is popularly known as horseweed. 7 This plant is a potential source of bioactive compounds 8 and several studies have reported the fungitoxic effects of its essential oils, [9][10][11] although the compounds responsible for such activity were not identified. Queiroz et al 7 found three fungitoxic compounds in dichloromethane extracts of C. canadensis specimens collected in the USA: (4Z)-lachnophyllum lactone (1), (4Z,8Z)-matricaria lactone (2), and (2Z,8Z)-matricaria acid methyl ester (3), whose chemical structures are shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Quanto à aplicação do hidrolato, verificou-se que em duas repetições, a reação das plantas foi considerada resistente e nas outras seis repetições a reação foi suscetível. Franzener et al (2007) avaliando a atividade antifúngica, antibacteriana e indutora da produção de fitoalexinas dos hidrolatos de Helietta apiculata (canela-de-veado), Conyza canadensis (buva) e Cymbopogon nardus (citronela) observaram que, independentemente da concentração utilizada, não se observou alteração sensível no crescimento micelial de Alternaria brassicae, demonstrando que há a presença dos compostos, porém em baixas concentrações. Em relação à aplicação do fungicida e do óleo essencial diluído do capim citronela na concentração de 2%, verificou-se que em quatro repetições, as plantas não apresentaram sintomas da doença (Tabela 1).…”
Section: Resultados E Discussão Ensaio I -Avaliação Do Efeito Curativunclassified
“…Hydrolate, also known as essence water, is produced during the extraction of essential oil from L. alba hydrolate (LAH), contains a small amount of essential oil and hydro soluble volatile compounds as acid, aldehyde and amines, having good commercial value (Franzener et al., ; Jeannot, Chahboun, Russel & Casabianca, ; Monsef‐Esfahani, Amanzade, Alhani, Hajimehdipour & Faramarzi, ).…”
Section: Introductionmentioning
confidence: 99%
“…Only a small number of studies have been published on hydrolates in animal farming: anthelmintic activity of Mentha villosa hydrolate in cattle (Nascimento, Furlong, Pimenta & Prata, ) and fungicidal and bactericidal properties of Helietta apiculata , Conyza canadensis and Cymbopogon nardus hydrolate (Franzener et al., ). However, no literature is available that describes the biology and activity of hydrolate and other aqueous extracts of plants, and their potential use as anaesthetics in aquaculture.…”
Section: Introductionmentioning
confidence: 99%